A Digitalized Voting System using Fingerprint Authentication - P, Ayisha; S, Karishma V; T, Renuka; Dileepkumar, Shruthi; E, Akhila (IRO Journal on Sustainable Wireless Systems, 2023)
Electronic voting, also referred to as "e-voting," has been used since the 1970s and has several benefits over paper-based systems, including increased efficiency and reduced mistake rates. However, there are still obstacles to the widespread adoption of these systems, particularly when it comes to enhancing their susceptibility to potential defects. To promote error-free, quick, and secure voting in elections, the study proposes an authentication system and a digitalized version of the current voting system in this research and suggests a fingerprint authentication method because fingerprints serve as a user’s unique and crucial form of identification. Aadhar database is stored in the system, and when a voter enters the polling booth, authentication and verification are done through a fingerprint scanner with the help of this. The voter can cast their vote digitally once the authentication and verification processes have been completed. If the voter has already voted, an error occurs and the ’voter has already voted’ message is displayed. Since the system already has the entire voter’s information, if there is a problem with the authentication procedure, the voter won’t be able to cast their vote. The proposed design has an easy-to-understand architecture and responds quickly. It makes trouble-free, easy, and accurate counting possible. This approach allows qualified voters to cast their ballots from anywhere in India.